Far-red triplet sensitized Z-to-E photoswitching of azobenzene in bioplastics. Issue 40 (5th October 2022) - Bharmoria, Pankaj; Ghasemi, Shima; Edhborg, Fredrik; Losantos, Raúl; Wang, Zhihang; Mårtensson, Anders; Morikawa, Masa-aki; Kimizuka, Nobuo; İşci, Ümit; Dumoulin, Fabienne; Albinsson, Bo; Moth-Poulsen, Kasper
Abstract : We report the first example of direct far-red endothermic triplet sensitized Z -to- E photoswitching of azobenzene derivative (Azo1) in a condensed phase of a liquid Azo1 co-assembled within a liquid surfactant-protein bioplastic film in air. Abstract : We report the first example of direct far-red triplet sensitized molecular photoswitching in a condensed phase wherein a liquid azobenzene derivative (Azo1) co-assembled within a liquid surfactant–protein film undergoes triplet sensitized Z -to- E photoswitching upon far-red/red light excitation in air. The role of triplet sensitization in photoswitching has been confirmed by quenching of sensitizer phosphorescence by Z -Azo1 and temperature-dependent photoswitching experiments. Herein, we demonstrate new biosustainable fabrication designs to address key challenges in solid-state photoswitching, effectively mitigating chromophore aggregation and requirement of high energy excitations by dispersing the photoswitch in the trapped liquid inside the solid framework and by shifting the action spectrum from blue-green light (450–560 nm) to the far-red/red light (740/640 nm) region.